Elite trips between Tunisia and Algeria and their impact on cultural and intellectual communication during the first half of the twentieth century - boudina, said (The Algerian Historical Journal, 2026)
This paper aims to demonstrate the contribution made by elite trips between Algeria and Tunisia. in order to strengthen cultural, intellectual and even reformist communication and interaction between the two countries in question, This was done through the news and information they were transmitting from their eyes or to the Tunisian and Algerian peoples alike. and creating convergence and solidarity in order to resist French colonialism culturally and intellectually, The press and education represented the pillars of that resistance, and colonialism seems to have been aware of that communication between the two peoples. This has led to the isolation of scientists and the confiscation of newspapers, preventing the movement of elites between Algeria and Tunisia in order to prevent such intellectual communication. Thus, a united front has been established against him in the Maghreb, undoubtedly undermining his presence and interests in the region. These flights have resulted in results; The most important of them is the consciousness of the two peoples on many important issues, such as the issues of affiliation and identity, the cultural influence of Tunisia on Algerians, represented by Tunisia's role and its olive university in the reformist renaissance in Algeria, as well as cultural and educational issues